Auntie Yang's great soybean picnic - Lo, Ginnie (Lee & Low Books, 2012)
"A Chinese American girl's Auntie Yang discovers soybeans-a favorite Chinese food-growing in Illinois, leading her family to a soybean picnic tradition that grows into an annual community event. Includes author's note and glossary"--Provided by publisher.